Pengaruh Kinerja Mengajar Guru Terhadap Kualitas Pembelajaran Di SMA Negeri 2 Banjar - Erna Maryati (PT. ALHAFI BERKAH INDONESIA, 2023)
The research is motivated by the not yet optimal teaching performance of teachers who play a very important role in supporting the quality of learning in schools. The aims of this research are: 1) To find out the teacher's teaching performance on the quality of learning in SMA Negeri 2 Banjar. 2) To determine the quality of learning in SMA Negeri 2 Banjar. 3) To determine the magnitude of the influence of teacher teaching performance on the quality of learning in SMA Negeri 2 Banjar. The research method used is descriptive method with a quantitative approach. The data collection technique was carried out by distributing questionnaires with a total of 56 respondents. Statistical data processing using SPSS 21.0. The results of the study show that 1) the teacher's teaching performance at SMA Negeri 2 Banjar is well achieved. It is evident from the results of processing the questionnaire with a value of 4691 being in good criteria. With the highest score on the teacher's voice indicator when teaching can be heard properly with a score of 257, and the indicator is dressed politely and neatly and deserves to be imitated with a score of 254. And the lowest score on the indicator is evaluating for preparing reports, evaluating using oral or written tests, and assessment of learning outcomes using educational assessment standards with a score of 224. 2) The quality of learning at SMA Negeri 2 Banjar has been well achieved. It is evident from the results of processing the questionnaire that a score of 2348 was obtained. The highest score was on the condition indicator in a clean and bright classroom with a score of 264 and the lowest score on the KBM indicator between teachers and students went smoothly and the learning atmosphere was not boring with time with a score of 224. 3) There is a positive influence of teacher teaching performance on the quality of learning. This is evidenced by the results of linear regression statistical calculations which state that any addition or increase in the teacher's teaching performance variable will have an impact on the quality of learning. The results of testing the hypothesis (t test) show that tcount is 3.682 > ttable 2.048, it can be concluded that the hypothesis is accepted. This means that there is a positive influence between the teacher's teaching performance variable (X) on the quality of learning (Y).